Lodovico Capponi and Florentine Funerary Politics - Maratsos, Jessica (The sixteenth century journal, 2020)
In order to parse the complicated relationships embodied in works of art patronage studies have become increasingly sophisticated in recent years. The role of social identity, as created, manipulated, and reified through acts of patronage, has become a particularly useful model for analysing visual culture in Renaissance Florence. This article explores the ways in which Lodovico di Gino Capponi utilized his artistic patronage, specifically of two different funerary monuments commissioned for himself and for his father-in-law, as a means of publicly demonstrating both his sensitivity to social hierarchies and his allegiance to the Medici. As a Florentine banker and merchant who made his career first in Rome before returning to his native city, Capponi's political ambitions were dependent upon his ability to navigate the complex relationships between the two cities in the uneasy stability established by the Medici the 1520s before the advent of the last Florentine Republic in 1527.